Kinetics Approach for Hydrogenation of Nitrobenzene to p-Aminophenol in a Four-Phase System - Li, Guangxue; Ma, Jianhua; Peng, Xinhua; Lv, Chunxu (Asian Journal of Chemistry, 2010)
The kinetics of the catalytic hydrogenation of nitrobenzene (NB) on a Pt/carbon catalyst in an acid medium to p-aminophenol (PAP), with aniline (AN) as a byproduct, was investigated in a batch reactor. By the elimination of the external and internal diffusion effects by good mixing, use of a superfine catalyst and the maintenance of a constant nitrobenzene concentration, the exponential macro-kinetics with respect to hydrogen pressure and reaction temperature are reported. In the kinetic equation, the reaction orders α, β for p-aminophenol (PAP) and aniline (AN) formation are 0.3251 and 2.8342, respectively, while the activation energies are EPAP 23.89 kJ/ mol and EAN 234.34 kJ/mol, respectively. The reaction results correspond well with experimental data.